Innovation activities of Ethiopian enterprises: current issues and recommendations - Anh, Le Lan; Samuel, Menelik (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
This research analysis of the second Ethiopian national innovation survey conducted for the year 2019. The result of this research provides information about the technological and non-technological innovations status, and the barriers of innovation among Ethiopian enterprises. Based on a list of 300,000 legally registered businesses oriented firms was obtained from different government ministries and organizations, this research’s findings indicate that only 19.4% of the sample enterprises were innovative. Disaggregation of innovation by types shows that the main types of innovation were product innovations, followed by process innovations; where about 96% of the innovative enterprises introduced technological innovations (product and/or process innovations). The innovative firms introduced a total of 686 innovations, out of which 56% were product innovations and 78.6% were technological innovations. The average number of innovations per enterprise was 4.64%. Code: 21072301